Activation of epiplexus macrophages in hydrocephalus caused by subarachnoid hemorrhage and thrombin - Wan, Yingfeng (CNS Neurosci Ther, 2019)
AIMS: We have found that hydrocephalus development in spontaneously hypertensive rats was associated with activation of epiplexus cells. The current study examined whether epiplexus cell activation occurs in a rat subarachnoid hemorrhage (SAH), whether activation would be greater in a subset of rats that developed hydrocephalus and the potential role of thrombin in epiplexus cell activation. METHODS: There were two parts in this study. First, an endovascular perforation was performed in rats to induce SAH. Second, rats received an intraventricular infusion of either thrombin or saline. Magnetic resonance imaging was used to measure the ventricular volumes. Immunofluorescence and immunohistochemistry were used to study epiplexus cell activation. RESULTS: Iba‐1, OX‐6, and CD68 were expressed in the epiplexus cells of the choroid plexus in sham‐operated rats. SAH increased Iba‐1 and CD68 immunoreactivity in epiplexus cells in addition to an increase in Iba‐1‐positive cell soma size. Those effects were greater in rats that developed hydrocephalus. Intraventricular thrombin mimicked the effects of SAH on epiplexus cell activation and hydrocephalus. CONCLUSION: This study supports the concept that epiplexus cell activation is associated with hydrocephalus development. Epiplexus cell activation may be in response to thrombin production after hemorrhage, and it may be a therapeutic target.